Methodological approaches for creating a system of security indicators for company´s personnel - KARZAEVA, N.N; DAVYDOVA, L.V (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article substantiates the need to identify principles for building a system of personnel security indicators. It has been found that there is no methodological basis for a system of personnel security indicators and there is a need to determine the composition of principles for their selection. The indicator should reflect the presence of the company’s security, which is a priority principle for establishing a system of indicators. A list of principles for such a system includes relevance to the goals, objectivity, measurability, complexity, permissible multicollinearity, variety, validity, simplicity. The article presents a system of personnel security indicators.RESUMEN El artículo corrobora la necesidad de identificar principios para construir un sistema de indicadores de seguridad del personal. Se ha encontrado que no existe una base metodológica para un sistema de indicadores de seguridad del personal y es necesario determinar la composición de los principios para su selección. El indicador debe reflejar la presencia de la seguridad de la empresa, que es un principio prioritario para establecer un sistema de indicadores. Una lista de principios para dicho sistema incluye relevancia para objetivos, objetividad, mensurabilidad, complejidad, multicolinealidad permisible, variedad, validez, simplicidad. El artículo presenta un sistema de indicadores de seguridad del personal.